The promotion effect of surface negative electrostatic field on the photogenerated charge separation of BiVO4 and its contribution to the enhanced PEC water oxidation1. Issue 14 (18th February 2015) - Xie, Mingzheng; Bian, Ji; Humayun, Muhammad; Qu, Yang; Feng, Yujie; Jing, Liqiang
<x xml:space="preserve">Abstract</x> The surface-carried negative charge of BiVO4 is favorable for the charge separation, leading to obviously enhanced visible-light-activity for PEC water oxidation.